2020
DOI: 10.1039/c9ra10077f
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in serum protein glycopatterns related to small cell lung cancer, adenocarcinoma and squamous carcinoma of the lung

Abstract: The main reason why lung cancer has maintained a high rate of morbidity and mortality is that its early diagnosis is difficult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
(42 reference statements)
1
5
0
Order By: Relevance
“…These unique findings could facilitate the study of biomarkers in the saliva of patients with ADC, SCC, and SCLC based on the precise alteration of galactosylated N‐glycans. Previously, with the use of serum microarray technology, we found that the expression levels of protein glycopatterns identified by BS‐I were significantly increased in the sera of SCLC compared to HV [20]. Our present findings were generally consistent with aberrant galactosylation in the serum of patients with SCLC, and we infer that this may be the result of many components of the blood entering the saliva by active transport, passive diffusion, or extracellular ultrafiltration [15].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These unique findings could facilitate the study of biomarkers in the saliva of patients with ADC, SCC, and SCLC based on the precise alteration of galactosylated N‐glycans. Previously, with the use of serum microarray technology, we found that the expression levels of protein glycopatterns identified by BS‐I were significantly increased in the sera of SCLC compared to HV [20]. Our present findings were generally consistent with aberrant galactosylation in the serum of patients with SCLC, and we infer that this may be the result of many components of the blood entering the saliva by active transport, passive diffusion, or extracellular ultrafiltration [15].…”
Section: Discussionsupporting
confidence: 84%
“…Our previous studies have shown that salivary proteoglycan patterns change differently in the saliva of patients with different diseases (e.g., Gastric Cancer, Breast Cancer, Liver Cancer) [17–19]. In our previous study, we found altered serum glycosylation levels in patients with benign pulmonary disease (BPD) and LC [20]. However, so far it is not clear whether there are associated glycosylation changes in the saliva of patients with lung disease.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study revealed that mutations in oncogenic drivers are associated with the progression and metastasis of LUAD, and the resulting alterations can be identified from circulating glycoproteins . Unique changes have been identified in serum glycoprotein glycoforms among small cell lung cancer (SCLC), LUAD, and squamous cell carcinoma (SCC) . Serum samples from lung cancer patients and age-matched controls revealed substantial increases in glycans containing sialyl Lewis X (sLe X ), monoantennary glycans, and highly sialylated glycans, whereas core-fucosylated biantennary N-glycans were diminished in lung cancer patients .…”
Section: Introductionmentioning
confidence: 99%
“…36 Unique changes have been identified in serum glycoprotein glycoforms among small cell lung cancer (SCLC), LUAD, and squamous cell carcinoma (SCC). 37 Serum samples from lung cancer patients and age-matched controls revealed substantial increases in glycans containing sialyl Lewis X (sLe X ), monoantennary glycans, and highly sialylated glycans, whereas core-fucosylated biantennary N-glycans were diminished in lung cancer patients. 38 However, using certain subsets of N-glycans, such as disialylated, tri-or tetra-antennary, or core-fucosylated glycans, as disease biomarkers results in poor sensitivity and specificity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…1 Lung cancer patients have a poor prognosis and a 5 year survival rate of less than 20%. 2 However, patients diagnosed at an early stage and who have surgery experience an 86% overall 5 year survival. Early diagnosis and therapy is critical to improving the survival rate of lung cancer.…”
Section: Introductionmentioning
confidence: 99%